2008
DOI: 10.1002/rnc.1399
|View full text |Cite
|
Sign up to set email alerts
|

A piecewise analysis method to stability analysis of linear continuous/discrete systems with time‐varying delay

Abstract: SUMMARYThe delay-dependent stability problem of linear continuous/discrete systems with time-varying delay is investigated based on a piecewise analysis method (PAM). In the method, the variation interval of the time delay is firstly divided into several subintervals. By checking the variation of the Lyapunov functional in every subinterval, some new delay-dependent stability criteria are derived. Several numerical examples show that our method can lead to much less conservative results than those in the exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
118
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(120 citation statements)
references
References 28 publications
0
118
1
1
Order By: Relevance
“…Using these methods, many stability criteria were derived by checking a variation of LKF in a whole interval of the time-delay. Contrary to this approach, in [24,25], in order to obtain some less conservative stability conditions, the interval of the time delay is divided into multiple equidistant subintervals and interval delay-dependent LKF (ID-D LKF) is constructed. By checking the variation of the ID-D LKF defined on the subintervals, some new delay-dependent stability criteria are derived.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using these methods, many stability criteria were derived by checking a variation of LKF in a whole interval of the time-delay. Contrary to this approach, in [24,25], in order to obtain some less conservative stability conditions, the interval of the time delay is divided into multiple equidistant subintervals and interval delay-dependent LKF (ID-D LKF) is constructed. By checking the variation of the ID-D LKF defined on the subintervals, some new delay-dependent stability criteria are derived.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the presented stability condition is much less conservative than the existing ones [1, 2, 6-9, 13-15, 22, 24], because it has a lower value of MAUB. The derived condition can be seen as an extension of the methods in [24,25], wherein the whole delay range is divided to n ≥ 2 equal subintervals. As the number of subintervals in [24,25] is greater than two, the decomposition approach is more complex and the resulting stability conditions are more conservative and difficult to implement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4], 변수추가 [10], 영(zero) 더 미(dummy) 함수 추가 [5], 그리고 구간 분할 [3] [7][8]등이 있 다. 이중 구간분할은 시간지연을 개의 부구간으로 나누고, …”
Section: 서 론unclassified
“…Yue et al [18] divided the variation interval of the time-delay into subintervals and employed a different LKF in every subinterval to derive some stability criteria for linear discrete-time systems with time-varying delay. Chen and Fong [19] converted the discrete-time system into an augmented one and developed some stability conditions that do not require the assumption of stability of the system when the delay vanishes to 0.…”
Section: Introductionmentioning
confidence: 99%